CHARACTERIZATION OF HYPERTENSION AND MIGRAINE IN RELATION TO SEX, AGE AND AB0 BLOOD GROUP AFFILIATION - Gergana Panayotova; Stanislav Ivanov; Evgeniya N. Ivanova (Peytchinski Publishing, 2022)
Among the group of multifactorial pathologies that are increasingly common and with high social importance in human populations are hypertension and migraine. Currently, about 27% of the world's adult population suffers from hypertension and about 11.4% - from migraine. Purpose: The aim of the present study is to investigate hypertension and migraine frequency among representatives of the reproductive population in Bulgaria and to characterize the potential relationships between these diseases and the factors of sex, age and AB0 blood groups. Material and methods: A total of 817 individuals aged between 18 and 59 years are included in the study. They voluntarily have filled out a questionnaire, giving disease information (hypertension and migraine) after they have been diagnosed by a physician. AB0-blood group affiliation has been determined in laboratory conditions by a routine technique. The statistical analysis has been performed using the IBM SPSS Statistics software package, version 22.0 Results: Differences in the frequency of hypertension and migraine have been found depending on sex, age and blood group of the individuals. It has been established that in the majority of the analyzed individuals, both diseases are simultaneously expressed. Conclusions: The risk of hypertension is higher for men and increases for both sexes over 44 years. The disease is more common among people in AB blood group. The risk of migraine is greater for women and increases for both sexes in the age group above 44 years. The disease is more common among people with blood types A and AB. Simultaneously appearance of both diseases is reported with the highest frequency in the representatives with blood group A, followed by those with blood group 0.